2014
DOI: 10.1158/1055-9965.epi-13-0515
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Ovarian Cancer Risk: A Systematic Review

Abstract: Ovarian cancer is a leading cause of gynecological cancer death. There is a need to identify modifiable dietary risk factors for this disease. To evaluate the role of diet in ovarian cancer risk we performed a PRISMA-directed systematic review that included prospective cohort studies with > 200 cases (n=24). Higher risk for ovarian cancer was shown for total, animal, and dairy fat (5 of 9 studies), as well as total nitrate and possibly total vitamin C. No associations were demonstrated for red meat, fiber, vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 57 publications
1
57
0
Order By: Relevance
“…The association between carotenoids and ovarian cancer risk is currently unclear in epidemiologic studies. Although study results have been mixed, prospective cohort studies have largely shown no association with the major carotenoids (17,19,(31)(32)(33) or specifically with b-carotene (34,35). Among the case-control studies that examined specific carotenoids, results have not been consistent regarding which showed statistically significant inverse associations (2,15,16,(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between carotenoids and ovarian cancer risk is currently unclear in epidemiologic studies. Although study results have been mixed, prospective cohort studies have largely shown no association with the major carotenoids (17,19,(31)(32)(33) or specifically with b-carotene (34,35). Among the case-control studies that examined specific carotenoids, results have not been consistent regarding which showed statistically significant inverse associations (2,15,16,(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…The prospective studies of dietary and supplemental vitamin E and ovarian cancer risk have shown mostly null results (17,(32)(33)(34)(35)45). The results of casecontrol studies are more mixed with some showing null (15,16,23,34,38) and others showing inverse associations (18,36,37,42,44). One case-control study found an inverse association with supplemental vitamin E intake that was not observed with dietary vitamin E (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current state of knowledge chemoprevention includes using agents that affect cell-cycle progression and apoptosis, signal transduction, oncogene activation, polyamine metabolism, angiogenesis, gap junctional intercellular communication, and more [6,7]. According to guidelines for cancer prevention published by the American Cancer Society Guidelines, one of the key lifestyle factors thought to modify cancer risk is a diet, especially that rich in plantorigin compounds [8][9][10][11]. Although nowadays natural therapies are being more and more often considered by physicians to be used even in cancer patients, together with targeted therapies, still little is known about their interaction with conventional chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that the observed pharmacological activities of flavonoids on ovarian cancer may depend on their structure [9,12]. Based on the range and structural complexity, flavonoids can be categorized into six major subclasses: flavones, isoflavones, flavonols, flavanones, anthocyanidins and flavan-3-ols [11,16], among which flavones, isoflavones and flavonols are reported in the highest amounts of consumption in the human diet and have biological activity in ovarian cancer [8,9,17,18].…”
Section: Introductionmentioning
confidence: 99%